Computational Thinking Ability of Students in Exponential Material Using Problem-Based Learning - Fitrisyah, Muhammad Aidil; Hapizah, Hapizah; Mulyono, Budi (Jurnal Riset Pendidikan Matematika, 2025)
Computational thinking is an important skill to have because it can help students to analyze and solve problems in a systematic, logical, and creative way, both in the world of computing and in everyday life. This study aims to identify the ability of computational thinking in students through problem-based learning on exponential topics. This study used descriptive qualitative method with 34 grade 10 students in one of the high schools in Palembang as research subjects, focusing on 3 students who have high, medium, and low abilities. The research was conducted in three stages: preparation, implementation, and data analysis. Data were collected through written tests and interviews to measure learners’ computational thinking skills. The results were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results showed that students’ computational thinking ability on exponential material was good in terms of pattern recognition and abstraction. However, for decomposition and algorithm skills, students still do not show their ability to solve problems systematically with the right answers.